Safety, efficacy and acceptability of medical abortion with mifepristone and misoprostol in Nepalese women - Shrivastava, Veena (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Unsafe abortion is a major health issue. Therefore safe abortion services which is effective. acceptable and techniquely easy to perform should be available. Aim- To confirm effectiveness, side effects, safety and patient satisfaction with medical termination of early pregnancy. Methods- It was a prospective study 150 women who were less than 63 days pregnant and consented for medical termination of pregnancy were given! 200mg 0 Mefepristone orally and 48 hrs later 800 micro gram Misoprostol was inserted vaginally. They were followed up in 14 days. Bleeding, pain G.I symptoms any other side effects were recorded. Abortion was complete or not was confirmed clinically and by USG. Failure and success was documented depending upon need for surgical evacuation. Results- The success rate with this regime was 92.6% and failure rate was 7.3%. There were no major side effects with Mifepristone. The average bleeding after misoprostol insertion was 10 days and 80% women had more bleeding than normal period. All of them had pain. Only 13.3% needed analgesic. women (96%) were satisfied with the method. Conclusion- combination of mifepristone and misoprostol is a safe and effective of early pregnancy Keywords- medical termination, pregnancy, mifepristone, misoprostol. doi:10.3126/njog.v2i2.1456 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 54 - 58